Evaluasi Peranan Penyuluh KB Dalam Pendampingan Keluarga Beresiko Stunting Di Kabupaten Serdang Bedagai Tahun 2022 - Emy Pardomuan Sinaga; Srimelda Bangun; Felix Kasim (BEST Journal (Biology Education, Sains and Technology), 2022)
Health is one of the important things and becomes the capital and goal of national development. In Indonesia, there are still a number of main health issues that must be focused on and resolved, namely stunting, maternal mortality and infant mortality, improvement of management of national health insurance, strengthening of health services, drugs and independence of drugs and medical devices. To deal with stunting, the Indonesian government stipulates a number of regulations to reduce the incidence of stunting, one of which is the role of health educators. This study aims to analyze the factors that support the success of family planning instructors in dealing with stunting in Serdang Bedagai 2022. The research method used is descriptive research with a qualitative approach. The informants of this research consisted of 6 people. Analysis of the data in this study using Trangulation. Based on the results of the study, it was found that the role of family planning instructors in stunting counseling to target groups has been running, among others, to prospective brides, prevention of stunting newborns, pregnant women, under-fives and toddlers as implementers of information communication and education and counseling in accelerating stunting reduction.In the village, the role of family planning instructors in surveillance has been running by conducting stunting audits so that data collection on families at risk of stunting and stunting is carried out, the supporting factor for the success of family planning instructors is the collaboration of various formal and informal parties to support government programs in reducing the risk of stunting or Concern for stunting